2017
DOI: 10.1080/14653125.2017.1346746
|View full text |Cite
|
Sign up to set email alerts
|

The effect of using mobile applications for improving oral hygiene in patients with orthodontic fixed appliances: a randomised controlled trial

Abstract: PI and GI all significantly decreased after 4 weeks of using active reminders of oral hygiene instructions on mobile application compared to verbal oral hygiene instructions. The study was registered at clinicaltrials.gov with number: NCT03109769.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
93
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(105 citation statements)
references
References 24 publications
5
93
0
7
Order By: Relevance
“…The participants' oral hygiene was signi cantly improved by the 'Oral and Denture Guide' PWA compared with that of the control group. This nding was in agreement with the ndings from the studies on oralhygiene focused applications [14,16]. Although no signi cant difference was found in the PI score between the PWA and control groups, gingival status may be a more reliable measurement of improvement in oral hygiene [38].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The participants' oral hygiene was signi cantly improved by the 'Oral and Denture Guide' PWA compared with that of the control group. This nding was in agreement with the ndings from the studies on oralhygiene focused applications [14,16]. Although no signi cant difference was found in the PI score between the PWA and control groups, gingival status may be a more reliable measurement of improvement in oral hygiene [38].…”
Section: Discussionsupporting
confidence: 91%
“…The mobile applications used in educating and motivating orthodontic patients to practise good oral hygiene showed excellent results [14][15][16]. Thus, they could be potentially used as a tool for chairside education and a take-home reference material for partial denture wearers.…”
Section: Introductionmentioning
confidence: 99%
“…Current awareness of apps is poor, despite this finding, 87% of participants in this study reported that they would be willing to use an app to aid with treatment. A number of studies (Zotti et al 2015, Li et al 2016, Alkadhi et al 2017, Lima et al 2018 have shown apps to be effective in orthodontics, however, there are a number of limitations of apps. Given the availability of apps targeted at orthodontic patients, there is a need to assess the quality of these apps and if appropriate navigate patients towards high quality, effective apps.…”
Section: Resultsmentioning
confidence: 99%
“…Alkadhi et al stated that PI and GI all significantly decreased after 4 weeks of using active reminders of oral hygiene instructions and this showed us the importance of four-week periodontal recall was enhanced the periodontal tissue health. 33 In the literature, it was seen that there was no uniformity in terms of the frequency of the intervention in a prophylaxis regime and OHI frequency varied between 3 weeks and 4 months. 34 The aim of our study was to evaluate the longterm possible effects of periodontal recall consisting of one-month or three-months intervals from the beginning of the fixed orthodontic treatment on gingival health.…”
Section: Discussionmentioning
confidence: 99%